A time-series analysis of the use of opioid medications in a network of Brazilian hospitals, 2009–2020Research in context - Romulo Mendonça Carvalho; Francisco Inácio Bastos; Maria Clara de Magalhães-Barbosa; Lucas Monteiro Bianchi; Jaqueline Rodrigues Robaina; Gustavo Rodrigues-Santos; Antônio José Ledo Alves da Cunha; Arnaldo Prata-Barbosa (The Lancet Regional Health. Americas)
Summary: Background: To date, no studies in Brazil have described the profile of hospital opioid use. This study aimed to describe the temporal evolution of opioid consumption in hospitalised patients in a Brazilian hospital network. Methods: This study describes a 12-year time-series (2009–2020) of hospital use of opioids in 28 hospitals of a private network in Brazil. More than four million prescriptions were analyzed using the Joinpoint Regression Program. Findings: Parenteral tramadol was the most consumed opioid, followed by parenteral fentanyl and parenteral morphine. Among enteral opioids, the most commonly used was codeine followed by tramadol. There were several variations in the use patterns for most medications, with periods of significant increases and decreases, but two opioids underwent considerable change: parenteral fentanyl, which doubled in consumption, especially during the COVID-19 pandemic, and enteral tramadol, which had a fourfold reduction over time. Enteral oxycodone, the pivot of the opioid crisis in the USA, was relatively little used in this series. Methadone, both parenteral and enteral, was seldom used at the hospitals under analysis, an indicator of a mild use of other opioids, before and/or during hospitalisation. Interpretation: Knowledge and documentation of the utilisation profile of this class of medication is relevant, given the concern that any increase in consumption at any point in the chain, including during hospitalisations, may trigger events of increased outpatient opioid use and potential misuse. Funding: Carlos Chagas Filho Foundation for Research Support in the State of Rio de Janeiro (FAPERJ, grant E-26/010.002428/2019) and IDOR Department of Pediatrics, Rio de Janeiro, RJ, Brazil.